(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Apolipoprotein B (APOB) is a component of chylomicrons, low-density lipoproteins (LDL), very low-density lipoproteins (VLDL), intermediate density lipoproteins (IDL) and functions as the main protein for transporting cholesterol to peripheral cells. APOB gene has an AT-rich VNTR site at its 3ʹ-untranslated region (3ʹ-UTR). APOB 3ʹ-VNTR alleles with ≥36 repeats have been shown to be strongly associated with increased serum lipid levels, gallstone formation and coronary artery disease. Objectives: To investigate any possible association of APOB 3ʹ-VNTR alleles with type 2 diabetes, BMI, systolic and diastolic blood pressure. Materials and methods: APOB 3ʹ-VNTR region in the DNA of non-diabetic controls and type 2 diabetic patients were amplified by polymerase chain reaction (PCR) and the numbers of core repeat in the amplified products were determined. Frequencies of the APOB alleles and genotypes among the controls and the patients were calculated and statistical analyses were performed. Results and discussion: Here we report for the first time that APOB 3ʹ-VNTR alleles have different distribution frequencies among type 2 diabetic and non-diabetic individuals. We also observed higher body mass index (BMI), systolic and diastolic blood pressures in individuals who had at least one APOB 3ʹ-VNTR allele with ≥35 repeats. Conclusion: Our study might bridge among the genetic signature of APOB 3ʹ-VNTR, high APOB protein level in blood, diabetes and other co-morbidities. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.71-77